Bund katholischer Ärzte: Homeopathic Conversion Therapists in 21st Century Germany - Borkens, Yannick (Frontiers in Sociology, 2022)
Even in modern Germany of the 21st century there is still homophobia and other intolerances towards different sexualities and genders. These are also evident in the presence of so-called conversion therapies, which are still offered although there are already legal efforts. Among those groups, the Bund katholischer Ärzte (Association of Catholic Doctors) is a unique curiosity. Although this group is no longer really active, it is currently moving into the German focus again due to criminal charges and reporting in the tabloid press. The aim of this publication is to bring the Bund katholischer Ärzte not only into a more scientific but also into a more international focus. Furthermore, it is an ideal example to show what strange effects homophobia can produce.